Estimating the level and distribution of global wealth, 2000-14 - James B. Davies; Rodrigo Lluberas; Anthony F. Shorrocks (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Davies et al. (2008, 2011) provided the first estimates of the global distribution of wealth, using 2000 as the benchmark year. These estimates have been revised and updated since 2010, and the purpose of this paper is to explain the ways in which the estimation methodology has evolved and improved in recent years. Further, the paper summarizes lessons learned about trends in the level and distribution of global wealth for the period 2000-14. Finally, the paper discusses the results in the context of the discourse provoked by Piketty (2014).
Keywords: D31; O15; 330; wealth inequality; global wealth; income distribution; econometrics